PERANAN STRATEGI TEKNOLOGI INFORMASI DAN STRATEGI BISNIS TERHADAP PENINGKATAN PEMBELAJARAN DI SMK PUSTEK SERPONG (Jurnal Pilar Nusa Mandiri, 2017)
Information technology is very important in influencing organizations’ performance to win over the competition. The role of information technology and the high investment resulted in the increasing demands to value provided by information technology in businesses. Human’s need associated with technology development also gives impact to education, and this will cause the emergence of a new paradigm in the education sector. This study uses Luftman Method and conducted at SMK PUSTEK SERPONG. The study finds that there is no harmony between the strategy of information technology and the business strategy in SMK PUSTEK SERPONG. Therefore, it is important to restructure these strategies and systemize the priority steps to improve the performance of the strategy of information technology and business strategy.
Keywords: Strategi Teknologi Informasi; Strategi Sistem Informasi; Peningkatan Pembelajaran; Learning Improvement